Management of gastric GIST removed through submucosal tunneling endoscopic resection and 5 year follow-up. Case report - Chirinos-Vega, Juan Antonio (2024)
We report the case of a 68-year-old female patient who had a gastrointestinal stromal tumor involving muscularis propria of the gastric body that was removed through submucosal tunneling endoscopic resection, with favorable follow-up after 5 years, with no signs of recurrence.